DAMPAK GOOD CORPORATE GOVERNANCE TERHADAP HUBUNGAN MOTIVASI MANAJEMEN LABA DENGAN PRAKTIK MANAJEMEN LABA - Ratnaning Tyasasih; Triska Dewi Pramitasari (Growth, 2018)
This study aimed to examine the effect of good corporate governance to earnings management motivation relationship with earnings management practices. The motivation of earnings management is divided into motivation debt as measured by the cost of debt and politically motivated violations as measured by the size of the company than the political cost calculation. Earnings management practices consist of earnings management in real terms measured from abnormal operating cash flow and abnormal production costs, as well as the accrual earnings management measured from the difference between the expected accrual and actual accrual. Meanwhile, good corporate governance role as a moderating variable that is measured by an index published by the company and IICD.Data were obtained from the annual financial statements of companies manufacturing the period 2013 - 2017. The population in this study are 136 companies listed in Indonesia Stock Exchange. Based on purposive sampling method, a sample obtained by three companies. The hypothesis in this study were tested using multiple regression analysis and regression stratified. Analysis of statistical tests in this study lead to the conclusion that the motivation of earnings management had no significant effect on earnings management in real terms and accrual earnings management. Statistical testing also concluded that good corporate governance can act as a moderating variable which can strengthen the relationship between the motivation of earnings management and earnings management practices both real and accruals.